Non-routine problem solving and strategy flexibility: A quasi-experimental study - Hüseyin Ozan Gavaz; Yeliz Yazgan; Çiğdem Arslan (Journal of Pedagogical Research, 2021)
This study aims to determine the effect of an instruction dealing with non-routine problem solving on fifth graders' strategy flexibility and success in problem-solving. For this aim, a quasi-experimental pre-test- post-test design without a control group was designed. The sampling method of the research is convenience sampling. There were 65 fifth graders (11-12 years of age) who came from two different classes of a public middle school located in Istanbul/Turkey. The instruction carried out by the first researcher in the students' classrooms lasted ten weeks (20 lesson hours). Pre-test and post-test consisted  of eight non-routine problems which can be solved by using guess and check, make a systematic list, work backward, look for a pattern, simplify the problem, and make a drawing strategies. The results showed that instruction that focuses on non-routine problem solving could improve students' strategy flexibility in this area. Besides, non-routine problem-solving instruction was associated with a significant positive improvement in students' problem-solving achievement. Based on these results, some educational implications and suggestions for future studies were discussed.